Hubungan Dukungan Keluarga Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa Di Rsud Moewardi Surakarta - Sukriswati, Indarti, Arif Widodo, A.Kep., M.Kes, EnitaDewi, S.Kep., Ns., MN (2016)
Hemodialysis actions indirectly affect the quality of life of patients with chronic renal failure. Quality of life is closely related to the support of family, because family support is the attitude, actions and acceptance of the families of patients who are sick. Family support can be given to patients with hemodialysis include emotional, esteem, information, instrumental, and support for social networks, all of which became a form of family support. The purpose of this study was to determine the relationship of family support and quality of life in hemodialysis patients in hospitals Moewardi Surakarta. The design study is a quantitative correlation method. The population in this study were 111 patients undergoing hemodialysis every week with a sample of 87 respondents. The independent variable in this study is the family support consisted of emotional support, appreciation, instrumental, information, and social networking. While the dependent variable is the quality of life research. Data were analyzed using contingency coefficient test. The study concluded that there is a relationship between family support with the quality of life of patients with chronic renal failure undergoing hemodialysis therapy with ρvalue = 0,000 <α (0.05) with Contingensi coefficient (C) of 0,447, it means that the better support a family, the more good quality of life. While the family support to support each dimension of the relation of emotional support and quality of life of patients with ρvalue = 0.000 <0.05 C at 0,483, the association awards support the quality of life of patients with ρvalue value = 0.000 <0.05 C of 0.504, instrumental support relationships with the quality of life of patients with ρvalue = 0.001 <0.05 C of 0.412, relationship information support and quality of life of patients with ρvalue = 0.000 <0.05 C of 0.460, social networking support relationships with quality of life of patients with ρvalue = 0.000 <0.05 C at 0.360. So it concluded the most closely related family support is the support award. Suggested families always provide emotional support, respect, instrumental, information and social network with both the hemodialysis patients that patients can improve their quality of life. For medical personnel need to maintain and improve services, and provide motivation for the family in providing support. For further research is expected to perform more complex research and provide benefits to the respondent.